2020
DOI: 10.1002/bip.23410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical rationalization for the base pairing abilities of inosine, guanosine, adenosine, and their corresponding 8‐oxo‐7,8‐dihydropurine, and 8‐bromopurine analogues within A‐form duplexes of RNA

Abstract: Inosine is an important RNA modification, furthermore RNA oxidation has gained interest due, in part, to its potential role in the development/progression of disease as well as on its impact on RNA structure and function. In this report we established the base pairing abilities of purine nucleobases G, I, A, as well as their corresponding, 8-oxo-7,8-dihydropurine (common products of oxidation at the C8-position of purines), and 8-bromopurine (as probes to explore conformational changes), derivatives, namely 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We have shown that the 8-oxo-purines (8-oxo-adenosine, 8-oxo-guanosine, and 8-oxo-inosine) all perform poorly as substrates for nonenzymatic RNA copying chemistry, regardless of whether they are present as activated mononucleotides, in the template, or at the end of a primer . Activated 8-oxo-purine monomers are incorporated very poorly in primer extension reactions, at rates comparable to those observed with mismatched canonical nucleotides, consistent with the strongly destabilizing effects of these modified nucleotides on duplex thermodynamic stability. …”
Section: Nucleobase Heterogeneitymentioning
confidence: 61%
“…We have shown that the 8-oxo-purines (8-oxo-adenosine, 8-oxo-guanosine, and 8-oxo-inosine) all perform poorly as substrates for nonenzymatic RNA copying chemistry, regardless of whether they are present as activated mononucleotides, in the template, or at the end of a primer . Activated 8-oxo-purine monomers are incorporated very poorly in primer extension reactions, at rates comparable to those observed with mismatched canonical nucleotides, consistent with the strongly destabilizing effects of these modified nucleotides on duplex thermodynamic stability. …”
Section: Nucleobase Heterogeneitymentioning
confidence: 61%
“…The former two are of interest given that 1) alkylative damage was recently explored alongside oxidative stress and m 1 G was one of the studied species; ( Yan et al, 2019 ) 2) both m 1 G and m 6,6 A are naturally occurring modifications with essential biological functions, particularly in the case of the former; ( McCown et al, 2020 ) and 3) the H-bonding pattern of these purine derivatives can serve to probe the hypothesis that, changes in H-bonding may play a role in the enzymatic stalling. Furthermore, 8-BrG is a chemically modified nucleoside that can be used to potentially provide information about conformational changes ( anti-syn ) around the glycosidic bond, ( Skinner et al, 2020 ) given that substitution at the C8-position of purine rings has been shown to favor the equilibrium towards the syn-isomer. Thus, we proceeded to incorporate each of these chemical probes/modifications into the same sequence context and obtained ONs 6–8 , which were converted to radiolabeled-phosphorylated ONs 6 ″– 8 ″, and treated with Xrn-1 as discussed previously ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…An NMR study reports a large predominance of SYN population and preference for the C2′-endo (SOUTH) sugar pucker conformation of inosine in solution [48]. Several theoretical and experimental studies have been conducted to investigate the structural and thermodynamic consequences due to the presence of inosine in RNA duplexes [6, [49][50][51][52][53]. Notably, the nearest neighbor thermodynamic parameters for I•U and I•C base pairs have been developed by Znosko and colleagues [50,51].…”
Section: Introductionmentioning
confidence: 99%